The Changes of Dorian’s Personality to be Narcissistic Caused by His Environment Reflected in Oscar Wilde’s Novel The Picture of Dorian Gray - OEMAYA, IRMA (Jurnal Ilmiah Mahasiswa FIB, 2014)
God creates human with the biological aspect as the foundation that build someone from the body, personality, character, etc, and biological is not the only factor that build some one’s character. There are some key factors, which provoke particular changes in human character, and these aspects can be divided into two groups, internal and external. Everyone has different personality and character, and they also have bad side and good side inside them, which is the most strongest side will be seen clearly as they wants.The Picture of Dorian Gray is a novel with uncommon theme or supernatural thing. Yet the real theme which is going to be analyzed deal with the change Dorian’s character a handsome young man from  innocent nature into an evily selfish person. Dorian Gray was a pure man until his meeting with Lord Henry brought him to realize that beauty is everything. The writer will use psychologycal approach to analyze possible cause of Dorian’s changes, and the psychological theory in this thesis is Narcissistic Personality Disorder.Later on Narcissistic Personality Disorder proves to be a complete and scientific theory to be used to analyze Dorian’s changes towards his attitudes. The thesis writer finds out that Dorian’s attitude after the change such as his selfishnessand show-off are actually caused by Narcissistic Personality Disorder. Keywords: Character, Attitude, Narcissistic Personality Disorder